1990
DOI: 10.1159/000247863
|View full text |Cite
|
Sign up to set email alerts
|

Leg Ulcers in a Patient with Spherocytosis: A Clinicopathological Report

Abstract: In a case of spherocytosis combined with ulcus cruris, Doppler sonography and phlebography revealed a chronic venous insufficiency, together with fibrinous precipitates in capillary and venous vessel walls. Some haemolysis and fragmentation of red cells in the biopsy was also observed. It is suggested that the haemodynamic alteration due to chronic venous insufficiency may have played the main role in the development of the ulcers, although the rheological disturbance caused by the spherocytosis may have had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…These inherited disorders of the red cell cytoskeleton lead to variable degrees of severity of haemolytic anaemia. Patients with these membranopathies have been reported to develop pulmonary thromboemboli (Hayag‐Barin et al , 1998), PH, and leg ulcers (Vanscheidt et al , 1990). It has been suggested that these complications are more frequent among patients that have undergone splenectomy (Schilling et al , 2008).…”
Section: Haemolytic Anaemias Associated With Pathological Vascular Comentioning
confidence: 99%
“…These inherited disorders of the red cell cytoskeleton lead to variable degrees of severity of haemolytic anaemia. Patients with these membranopathies have been reported to develop pulmonary thromboemboli (Hayag‐Barin et al , 1998), PH, and leg ulcers (Vanscheidt et al , 1990). It has been suggested that these complications are more frequent among patients that have undergone splenectomy (Schilling et al , 2008).…”
Section: Haemolytic Anaemias Associated With Pathological Vascular Comentioning
confidence: 99%
“…Leg ulcerations are a serious and debilitating complication of sickle cell disease (SCD) and other hemolytic anemias associated with markers of severe disease and early mortality, both in the United States and other countries . Their etiology and evolution is multifactorial and not completely characterized, but compromised blood supply secondary to vaso‐occlusion has been considered a determinant factor in their occurrence and delayed healing . Most recently endothelial dysfunction and thrombosis have been hypothesized to be contributing factors for this and other end‐organ damage in SCD .…”
Section: Introductionmentioning
confidence: 99%
“…Such localized hemolysis has been shown within and outside of capillaries by electron microscopy in the vicinity of leg ulcers of a patient with spherocytosis. 10 Although 2% of patients with spherocytosis develop leg ulcers, 12 the clinical finding of recurrent pseudoerysipelas as seen in our patient has not been reported thus far. Because our patient had mild spherocytosis based on hematologic and serologic findings, 1 we hypothesize that his family carries an unknown mutation for a mild autosomal dominant phenotype.…”
Section: Discussionmentioning
confidence: 49%
“…1 The most frequently reported dermatologic complication of hereditary spherocytosis, reported in fewer than 2% of the patients, are leg ulcers at atypical locations, such as the back of the feet in patients withouth splenectomy. [10][11][12][13] Healing of refractory leg ulcers was reported after splenectomy. 11,14 The pathogenesis of the more commonly described leg ulcers in congenital spherocytosis is unknown.…”
Section: Discussionmentioning
confidence: 99%